Cheap and Secure Web Hosting Provider : See Now

Why does this grammar derive into $\beta \alpha ^*$ instead of $\alpha ^* \beta$?

, , No Comments
Problem Detail: 

In this video clip the teacher presents a grammar $A \rightarrow A \alpha | \beta$ and after providing the parse tree explains that the regular expression for the language generated is represented as $\beta \alpha ^*$.

Why isn't it $\alpha ^* \beta$ instead? Isn't the grammar left-recursive into terminal $\alpha$ and once terminal $\beta$ is reached the string ends?

Asked By : Dave
Answered By : Rick Decker

Try some derivations:

  • $A\Rightarrow \beta$
  • $A\Rightarrow A\alpha\Rightarrow \beta \alpha$
  • $A\Rightarrow A\alpha\Rightarrow A\alpha\alpha\Rightarrow \beta \alpha\alpha$

The pattern is clear: starting from $A$, we'll generate strings of the form $\beta\alpha\dotsc\alpha$, in other words, $\beta\alpha^*$. Since at any stage we have $A$ on the left of the sentential form, we'll eventually generate strings with $\beta$ on the left.

If the grammar had been $A\rightarrow \alpha A\mid \beta$, then we'd derive strings of the form $\alpha^*\beta$.

Best Answer from StackOverflow

Question Source : http://cs.stackexchange.com/questions/66884

3200 people like this

 Download Related Notes/Documents

0 comments:

Post a Comment

Let us know your responses and feedback